Relationships between occupational history and serum concentrations of organochlorine compounds in exocrine pancreatic cancer. Issue 5 (23rd November 2010) - Bosch de Basea, Magda; Porta, Miquel; Alguacil, Joan; Puigdomènech, Elisa; Gasull, Magda; Garrido, José A; López, Tomàs; ,
Abstract : Background: Previous studies investigating associations between occupational history and risk of exocrine pancreatic cancer (EPC) did not use biomarkers of exposure. The only two studies that measured internal concentrations of organochlorine compounds (OCs) in EPC did not analyse their relationship with occupation. Objective: To analyse the relationship between occupational history and blood concentrations of seven OCs in patients with EPC. Methods: Incident cases of EPC were prospectively identified, and during hospital admission were interviewed face-to-face on occupational history and life-style factors (n=135). Occupations were coded according to the International Standard of Occupations 1988. Some occupational exposures were also assessed with the Finnish job-exposure matrix (Finjem). Serum concentrations of OCs were analysed by high-resolution gas chromatography with electron-capture detection. Results: Craftsmen and related trades workers had significantly higher concentrations of polychlorinated biphenyl (PCB) congeners 138, 153 and 180. Years worked in agriculture did not influence concentrations of p, p'-DDT, p, p'-DDE, hexachlorobenzene or β-hexachlorocyclohexane. Subjects who ever worked in agriculture had lower concentrations of PCBs (all p<0.05). Occupational exposure to lead, nickel and low frequency magnetic fields was significantly associated with higher concentrations of PCBs. Conclusions: Certain occupations were associated with higher concentrations of PCBs, suggesting that these compounds may account for some increased risks found in previous studies. The lack of association between work in agriculture and concentrations of OC pesticides is consistent with occupation playing a lesser role than diet in influencing OC concentrations. Occupational studies on the relationships among exposure to industrial agents and EPC risk may need to consider adjusting for exposure to PCBs.